Competitiveness and FDI inflows in ASEAN member countries - Dewa Gede Sidan Raeskyesa; Reinardus Adhiputra Suryandaru (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The goal of this study is to investigate the empirical effect between competitiveness and FDI inflow in ASEAN member countries over the period 2007-2017. Design/methodology/approach: The effect of competitiveness and foreign direct investment (FDI) was investigated by using Pearson correlation and panel data analysis. The fixed effect and random effect models were applied, followed by the Hausman test, which led us to use the fixed effect model. Finding: The study revealed that the majority of ASEAN countries have a strong and positive association between competitiveness and the FDI inflow. Specifically, variable institutions, market size, health, and primary education had a significant effect on attracting inward foreign direct investment in the region. Research limitations/implications: In order to attract more foreign direct investment, it is highly suggested the ASEAN countries enhance their institution quality and improve the human capital through health and basic education. Originality/value: Our study enriches the literature on globalization and competitiveness by focusing on the regional empirical effect between each variable from the Global Competitiveness Index and the FDI inflow exclusively in countries within the ASEAN region.
Keywords: F02; F23; O19; 330; FDI; International Competitiveness; Foreign Investment